(untitled) (Journal of Hama University, 2022)
Introduction: Pulpotomy is one of the most widely accepted clinical procedures for treating cariously exposed pulp in primary teeth. The rationale of this technique is based on the healing ability of the radicular pulp tissue following surgical amputation of the affected or infected coronal pulp. Aim: To compare the efficacy of (avzoe) with (zoe) as a sub-base material in primary teeth pulpotomy clinically and radiographically. Materials and Methods: The study sample included 33 healthy children (5-9 years), visiting pediatric dentistry department. Each child had primary canines or molars indicated for extraction as a part of orthodontic treatment. The study sample consisted of 41 primary teeth divided into two groups. Group I: included 18 primrary teeth in which aloe vera gel was used as a pulpotomy medicament, and a mixture of aloe vera gel with zinc oxide and eugenol (avzoe) as a sub-base material. Group II: included 23 primary teeth in which formocresol was used for pulpotomy, and a mixture of zinc oxide and eugenol cement (zoe) as a sub-base material. Amalgam was used as a final restoration. Clinical and radiographic evaluation was performed after one, six and twelve months. Results: The clinical and radiographic success percentage in the (avzoe) group was 77.8% after one year of observation compared to 78.3% in the (zoe) group. Conclusion: This study did not show significant clinical and radiographic differences between (avzoe) and (zoe) in pulpotomy on primary teeth.